The Influence of Migration Crisis in Europe on EU-Turkey Relations - Pavel P. Timofeyev (Vestnik MGIMO-Universiteta, 2016)
The paper examines the impact of the migration crisis in the EU on the European Union's relations with Turkey. It is shown that for a number of reasons, including a result of EU actions taken from 2011 to 2015, EU has experienced an influx of migrants on a number of routes from the Western to the Eastern Mediterranean. The largest of them fell on Turkey, which has tried to use this factor to exert pressure on the EU in order to obtain economic and political preferences. The author examines the development of the EU migration policy in the context of the crisis, its trying to bring Turkey to cooperate and difficult negotiations, which took place at the summits of the EU-Turkey at the end of 2015. There have been disagreements among the EU countries, and the time factor, which Turkey took advantage of, advancing conditions for the closure of borders to Europe for migrants. Facing the influx of migrants the EU had to agree with a number of conditions, though not with all. The author shows that the agreement reached by the country in March 2016 is not universal, and a number of issues important to the resolution of the crisis, are waiting to be decided upon. However, according to the author, the development of the current crisis can lead both to the reform of the migration and border policy within the EU, and to restarting relations with Turkey. Though guessing on possibilities on Turkey's entry to the EU in the near future is still premature.